Atomic-scale origin of shear band multiplication in heterogeneous metallic glasses. (15th March 2020) - Şopu, D.; Scudino, S.; Bian, X.L.; Gammer, C.; Eckert, J.
Abstract: Using molecular dynamics simulations, we provide an atomistic description of the shear band multiplication mechanisms in a heterogeneous metallic glass consisting of two distinct amorphous regions with different amounts of free volume and degrees of short-range order. The structural differences and elastic fluctuations encountered by the developing shear band while crossing the interface between the two regions alter the autocatalytic activation of the shear transformation zones (STZs) and, subsequently, lead to shear band branching. The two-unit STZ-vortex mechanism sheds light on the correlation between the strain distribution during tensile deformation and the directional characteristics of the STZ activation process. Graphical abstract: Image, graphical abstract